Quad-Band Polarization-Insensitive Square Split-Ring Resonator (SSRR) with an Inner Jerusalem Cross Metamaterial Absorber for Ku- and K-Band Sensing Applications - Mohammad Lutful Hakim; Touhidul Alam; Mohammad Tariqul Islam; Mohd Hafiz Baharuddin; Ahmed Alzamil; Md. Shabiul Islam (Sensors, 2022)
The development of metamaterial absorbers has become attractive for various fields of application, such as sensing, detectors, wireless communication, antenna design, emitters, spatial light modulators, etc. Multiband absorbers with polarization insensitivity have drawn significant attention in microwave absorption and sensing research. In this paper, we propose a quad-band polarization-insensitive metamaterial absorber (MMA) for Ku- and K-band applications. The proposed patch comprises two square split-ring resonators (SSRR), four microstrip lines, and an inner Jerusalem cross to generate four corresponding resonances at 12.62 GHz,14.12 GHz, 17.53 GHz, and 19.91 GHz with 97%, 99.51%, 99%, and 99.5% absorption, respectively. The complex values of permittivity, permeability, refractive index, and impedance of MMA were extracted and discussed. The absorption mechanism of the designed MMA was explored by impedance matching, equivalent circuit model, as well as magnetic field and electric field analysis. The overall patch has a rotational-symmetrical structure, which plays a crucial role in acquiring the polarization-insensitive property. The design also shows stable absorption for both transverse electric (TE) and transverse magnetic (TM) modes. Its near-unity absorption and excellent sensing performance make it a potential candidate for sensing applications.